The wisdom of Archilochus: didactic intertexts in early Greek poetry - Swift, L (Cambridge University Press, 2024)
This chapter investigates Archilochus’ relationship to the tradition of wisdom literature, using the poet as a case study for how we can think about inter-generic and intertextual relationships so early in the Greek literary tradition. Having established that Archilochus is familiar with (and expects his audience also to know) the conventions of didactic moralising, the chapter discusses the case for a stronger proposition: that his poetry demonstrates a specific relationship with the poems of Hesiod. The chapter examines some fragments which demonstrate the best case for an intertextual relationship (frr. 196a, 195, 177) and discusses how reading these through a Hesiodic lens enhances our understanding of what the poems aim to do and how they fit into Archilochus’ broader rhetorical strategy.